PROBLEMS AND PROSPECTS OF TOURIST INSURANCE - ILNITSKA-GYKAVCHUK, Galina (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article discusses the types of insurance in tourism. Based on the analysis of the insurance market of Ukraine, it was established that the number of insurance companies decreased by almost three times during the years 2015-2022, and 25 insurance companies worked in the field of tourism in 2023. It was revealed that the following companies are the leaders in the travel insurance market: European Travel Insurance, ARX, VUSO, PZU Ukraine. The factors that hold back the development of tourism insurance are highlighted: military actions due to Russia’s invasion of Ukraine, political instability; decrease in the number of tourists, low solvency of the population; imperfect legal framework; poor awareness of the population in the field of tourism insurance; public distrust of insurance companies; a narrow range of insurance services in the field of tourism insurance; incomplete and untimely fulfillment of obligations to policyholders; limited scope of insurance protection due to reduction of insurance prices by insurers; decrease in the quality of insurance products; insufficient professional level of insurance company specialists; overall low development of the country’s insurance market. The main trends in the field of insurance in Ukraine are revealed: individual policies for certain tourist segments, use of artificial intelligence, transformation of products into the format of electronic policies, blockchain technologies. Directions for solving problems in the field of insurance in tourism are indicated: improvement of the regulatory and legal framework; ensuring political stability, increasing economic development in the state; training of highly qualified personnel in the field of insurance; improvement of insurance culture; creation of protective mechanisms for tourists; assistance from the state to the development of the insurance market in Ukraine; improvement of the risk management mechanism; increasing public trust in insurance companies; expanding the list of insurance services and improving their quality.